A bionic scale super wear-resistant agent for textile leather

By grafting the water-soluble polysiloxane particle brush structure on textile leather, the bionic scale super wear resistance is formed, and the problems of harsh reaction conditions and insufficient adhesion in the prior art are solved. It achieves high adhesion, wear resistance and waterproof and pollution-resistant effects.

CN114657772BActive Publication Date: 2024-12-17ANHUI SINOGRACE CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210282943.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-22
Publication Date
2024-12-17
Estimated Expiration
2042-03-22

AI Technical Summary

Technical Problem

During the use of existing textile leather wear-resistant agents, there are problems such as harsh reaction conditions, complex process, poor wear resistance and volatile prepolymers, and the common wear-resistant agents of inorganic oxide powder are used. Instability and lack of adhesion.

Method used

Using the grafted water-soluble polysiloxane particle brush structure of silica nanosheets, the water-soluble polysiloxane is modified on the surface of silica nanosheets through click chemical reaction to form a bionic scale super wear resistance, with excellent wear resistance Properties, gloss, wet and dry resistance, flexibility and waterproof and pollution resistance.

Benefits of technology

A bionic scale structure with high adhesion, wear resistance, gloss and waterproof is achieved on the surface of textile leather, which improves the weather resistance and feel of the product, while reducing process complexity and pollution risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114657772B_ABST
    Figure CN114657772B_ABST
Patent Text Reader

Abstract

The invention discloses a bionic scale super wear-resistant agent for textile leather, which is a silica nanosheet grafted water-soluble polysiloxane particle brush, comprising silica nanosheet powder; and water-soluble polysiloxane, wherein the water-soluble polysiloxane is chemically grafted on the surface of the silica nanosheet powder. The particle brush structure of water-soluble polysiloxane is chemically grafted on the surface of the silica nanosheet. After the super wear-resistant agent is applied, a bionic scale structure can be formed on the surface of the textile leather, giving the textile leather excellent wear resistance, glossiness, dry and wet rubbing resistance, and flexibility, and also has excellent adhesion and waterproof and anti-pollution capabilities, while increasing the feel of the product, making the product softer, more natural, smoother and more delicate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano materials for textiles and leathers, and particularly relates to a bionic scale super wear resistant agent for textiles and leathers, and also relates to a preparation method of the bionic scale super wear resistant agent. Background Art

[0002] With the application of textile leather, in order to improve its wear resistance, a certain proportion of wear-resistant agent is usually added to the textile leather. Common inorganic oxide powders, such as silicon oxide, aluminum oxide or titanium oxide powder and other high-hardness wear-resistant materials, are not very wear-resistant if they are directly used as wear-resistant agents; and if these oxide wear-resistant powders are reacted with coupling agents to make water-soluble wear-resistant agents, the products are mostly emulsions, which will react with other components during use, resulting in instability and limitations. At the same time, the groups in the coupling agent that are not completely reacted may also react with the yarn in the textile leather to cause incomplete desizing; in addition, if the wear-resistant powder is reacted with a chemical substance with low surface energy, the resulting wear-resistant agent is non-water-soluble. Due to its low water solubility, it is easy to cause a weak interaction with textile leather and greatly reduce its weather resistance.

[0003] In view of the above problems, the most effective solution is to physically or chemically react wear-resistant powder with polymer materials to form an organic-inorganic composite wear-resistant agent. For example, the Chinese patent application with publication number CN108221398A discloses a silicone rubber leather with good wear resistance and its coating process, but the solution generally requires a large amount of application to achieve the wear-resistant effect; another example is a Chinese patent application with publication number CN113529408A discloses a new type of water-based wear-resistant agent and its application, but its reaction conditions are harsh, the polymer and inorganic part have weak interaction, and the weather resistance is poor.

[0004] In summary, the current solutions have problems such as harsh reaction conditions or complex processes, poor wear resistance, and the use of some volatile prepolymers, which are prone to pollution. Summary of the invention

[0005] In view of this, it is necessary for the present invention to provide a bionic scale super wear-resistant agent for textile leather, which is a silica nanosheet grafted water-soluble polysiloxane particle brush structure, with double-bond modified thin layer silica nanosheets as the main wear-resistant filler, and water-based polysiloxane is grafted on the surface of the silica nanosheets. After the wear-resistant agent is applied, a super wear-resistant agent with a bionic scale structure can be formed on the surface of the textile leather, which has excellent wear resistance, gloss, resistance to dry and wet rubbing, flexibility, and also has excellent adhesion and waterproof and anti-pollution capabilities. At the same time, it can increase the feel of the product, making the product softer, more natural, smooth and delicate.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides a bionic scale super wear-resistant agent for textile leather, which is a silica nanosheet grafted water-soluble polysiloxane particle brush, comprising:

[0008] Silica nanosheet powder;

[0009] and water-soluble polysiloxane, wherein the water-soluble polysiloxane is chemically grafted on the surface of the silicon dioxide nanosheet powder.

[0010] In a further embodiment, the silicon dioxide nanosheets have a thickness of 3-100 nm and a size of 0.5-50 μm.

[0011] In a further embodiment, the molecular weight of the water-soluble polysiloxane is 100-4000.

[0012] The present invention further provides a method for preparing a super wear-resistant agent for textile leather, comprising the following steps:

[0013] Providing silica nanosheet powder and liquid mercapto-terminated water-soluble polysiloxane;

[0014] Obtaining double-bond modified silica nanosheet powder particles;

[0015] The double-bond modified silica nanosheet powder particles are mixed into the liquid mercapto-terminated water-soluble polysiloxane, and an ultraviolet light initiator is added. After being mixed evenly, the mixture is treated with ultraviolet light, and a paste-like wear-resistant agent is obtained through a click chemical reaction.

[0016] In a further embodiment, the preparation method of the double bond modified silica nanosheet powder particles is:

[0017] Dispersing silica nanosheet powder in an alcohol-water mixed solution with a pH of 8-12 to form a dispersion;

[0018] A silane coupling agent containing double bonds is added to the dispersion to react and modify the silicon dioxide nanosheet powder at room temperature to obtain the double bond-modified silicon dioxide nanosheet powder particles.

[0019] In a further embodiment, in the alcohol-water mixed solution, the volume ratio of alcohol to water is 1-20, and the alcohol is a water-soluble low molecular weight alcohol with a molecular weight of 46-1000.

[0020] In a further embodiment, the amount of the double-bond-containing silane coupling agent added is 0.1%-20% of the mass of the silicon dioxide nanosheet powder;

[0021] The double bond-containing silane coupling agent is selected from one or more of γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, vinyltrimethoxysilane, and vinyltri(b-methoxyethoxy)silane.

[0022] In a further embodiment, the amount of the liquid mercapto-terminated water-soluble polysiloxane added is 30%-400% of the mass of the silicon dioxide nanosheet powder, wherein the molecular weight Mn of the water-soluble polysiloxane is 100-4000.

[0023] In a further embodiment, the amount of the ultraviolet light initiator added is 10% to 40% of the molar amount of the liquid mercapto-terminated water-soluble polysiloxane;

[0024] The ultraviolet light initiator is selected from one or more of isopropylthioxanthinequinone, 4-methylbenzophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 1-hydroxy-cyclohexyl-phenyl ketone.

[0025] In a further embodiment, in the step of ultraviolet light treatment, the power of the ultraviolet light is 35-100W and the time is 1-24h.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The bionic scale super wear-resistant agent in the present invention is a silica nanosheet grafted polysiloxane particle brush. The overall flaky structure makes it more adhesive than the same type of spherical wear-resistant agent, not easy to fall off and has a wide range of applications; and the micron-sized flaky structure and the material with a small refractive index make the wear-resistant agent have a pearlescent effect, which can effectively increase the glossiness without adding other substances; the silica nanosheet is thin, has soft mechanical properties and high wear resistance. In addition, the super wear-resistant agent can adhere to the application surface to form a bionic scale structure, and it itself has a lubricating component, which can effectively reduce the friction coefficient, so it will be more wear-resistant.

[0028] The present invention uses water-soluble polysilane in the preparation of the super wear-resistant agent to make it have dry and wet rubbing resistance and flexibility; the particle brush with a scale-like structure has strong barrier properties and waterproof and anti-pollution capabilities on the basis of moisture permeability due to the special structure.

[0029] The raw materials used to prepare the super wear-resistant agent are low in price, the preparation process is simple, low in energy consumption, and low in pollution; the click chemistry grafting method used has high atomic utilization and no solvent pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The figure is a schematic diagram of the preparation process of the bionic flake super wear-resistant agent of the present invention;

[0031] Figure 2It is a schematic diagram of the principle of the bionic scale super wear-resistant agent in the present invention;

[0032] Figure 3 This is a SEM image of the silicon dioxide nanosheet powder used in Examples 1-3 of the present invention;

[0033] Figure 4 This is a SEM image of the bionic flake super wear resistant agent prepared in Example 1;

[0034] Figure 5 This is a SEM picture of the bionic scale super wear-resistant agent prepared in Example 2 after being applied to the leather surface;

[0035] Figure 6 This is a SEM picture of the bionic scale super wear resistant agent prepared in Example 3 after being applied to the surface of textile fibers. DETAILED DESCRIPTION

[0036] Embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0038] The first aspect of the present invention provides a bionic scale super wear-resistant agent for textile leather, which is a silica nanosheet grafted water-soluble polysiloxane particle brush, specifically, it includes silica nanosheet powder; and water-soluble polysiloxane, the water-soluble polysiloxane is chemically grafted on the surface of the silica nanosheet powder particles. This structure makes the whole body flaky, and its adhesion is stronger than that of the same type of spherical wear-resistant agent, it is not easy to fall off and has a wide range of applications, and the bionic scale super wear-resistant agent forms a structure similar to the surface of squamates after being applied to the surface of the material, so it has a high wear-resistant effect; in addition, the bionic scale super wear-resistant agent has a good affinity with polymer materials and has its own lubricating components, so it reduces the friction coefficient and improves the wear-resistant effect.

[0039] In a further embodiment, the size of the silica nanosheets in the silica nanosheet powder of the present invention can be adjusted or selected according to actual conditions. In one or more embodiments of the present invention, the thickness of the silica nanosheets is 3-100nm and the size is 0.5-50μm; preferably, the thickness of the silica nanosheets is 5nm and the size is 0.5-1μm.

[0040] In a further embodiment, water-soluble polysiloxane is grafted onto the surface of the silica nanosheets to impart dry and wet abrasion resistance and flexibility to the super wear-resistant agent. In some specific embodiments of the present invention, since a large molecular weight leads to a large viscosity and increases the difficulty of operation, it is preferred that the molecular weight of the water-soluble polysiloxane is 100-4000, and the water-soluble polysiloxane within this molecular weight range can further improve the adhesion of the super wear-resistant agent.

[0041] The second aspect of the present invention provides a method for preparing a bionic scale super wear-resistant agent for textile leather, Figure 1 The main steps of the preparation method are as follows:

[0042] Provide silica nanosheet powder and liquid thiol-terminated water-soluble polysiloxane

[0043] The thickness of the silicon dioxide nanosheet powder in the present invention is 3-100nm, and the size is 0.5-50μm; preferably, the thickness of the silicon dioxide nanosheet is 5nm, and the size is 0.5-1μm, which can be selected according to actual conditions; and the liquid thiol-terminated water-soluble polysiloxane refers to the water-soluble polysiloxane containing thiol groups in the end group, thereby providing a basis for subsequent reactions.

[0044] Preparation of double bond modified silica nanosheet powder particles

[0045] Double-bond modified silica nanosheet powder particles are prepared so that the surface of the silica nanosheet has unsaturated bonds to achieve subsequent reaction with liquid thiol-terminated water-soluble polysiloxane.

[0046] Double bond-modified silica nanosheet powder particles can be prepared by conventional methods in the art. According to an embodiment of the present invention, silica nanosheet powder is first dispersed in an alcohol-water mixed solution with a pH of 8-12, preferably a pH of 9-11, to form a dispersion; then a double bond-containing silane coupling agent is added to the dispersion to react and modify the silica nanosheet powder at room temperature to prepare double bond-modified silica nanosheet powder particles. Among them, in the alcohol-water mixed solution, the volume ratio of alcohol to water is 1-20, and the alcohol used is a water-soluble small molecule alcohol with a molecular weight between 46 and 1000. Specific examples include but are not limited to ethanol, ethylene glycol, butanediol, etc.; the pH control of the alcohol-water mixed solution can be achieved by adding a base, and the base is an organic base or an inorganic base, which are conventional compositions in the art. For example, the organic base can be selected from ethylenediamine, triethylamine, triethanolamine, tetraethylenepentamine, diethylenetriamine, triethylenetetramine, trimethylolaminomethane, tetrahydroxyethylethylenediamine, tetrahydroxypropylethylenediamine, tetraethylethylenediamine, 1,8-bis(dimethylaminonaphthalene), and one of imidazole. The inorganic base is one of ammonia water, sodium hydroxide, and potassium hydroxide. It can be understood that the concentration and amount of the base are not specifically limited here, as long as the purpose of adjusting the pH of the system to the required range can be achieved.

[0047] Furthermore, the double bond-containing silane coupling agent in the present invention is selected from γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltri(b-methoxyethoxy)silane, etc., preferably γ-methacryloxypropyltriethoxysilane; the amount of the double bond-containing silane coupling agent can be adjusted according to the amount of silica nanosheet powder and polysiloxane, without special limitation. In one or more embodiments of the present invention, the amount of the double bond-containing silane coupling agent added is 0.1%-20% of the mass of the silica nanosheet powder particles.

[0048] Preparation of silica nanosheet-grafted water-soluble polysiloxane particle brushes

[0049] The double-bond modified silica nanosheet powder particles prepared above are mixed into a liquid thiol-terminated water-soluble polysiloxane, and a UV initiator is added. After being mixed evenly, the mixture is treated with UV light, and a paste-like anti-wear agent is obtained through a click chemical reaction. Specifically, since the surface of the silica nanosheet powder particles contains an unsaturated bond-double bond, under the initiation of the UV initiator and UV light, the thiol contained in the end group of the water-soluble polysiloxane reacts with the double bond through a click chemical reaction, thereby grafting polysiloxane on the surface of the silica nanosheet to form a particle brush structure. The particle brush is in the form of a sheet as a whole, with a thickness of 3-100nm and a size between 0.5-4μm.

[0050] Furthermore, the amount of water-soluble polysiloxane added in the present invention can be adjusted according to actual needs. In some specific embodiments of the present invention, the amount of liquid mercapto-terminated water-soluble polysiloxane added is 30%-400% of the mass of the silica nanosheet powder, wherein the molecular weight Mn of the water-soluble polysiloxane is 100-4000.

[0051] It is understandable that the ultraviolet light initiator is a conventional choice in the art, and its dosage can be adjusted according to the reaction conditions, so there is no special limitation. In one or more embodiments of the present invention, the amount of the ultraviolet light initiator added is 10%-40% of the molar amount of the liquid mercapto-terminated water-soluble polysiloxane; specific examples of the ultraviolet light initiator include, but are not limited to, one or more of isopropylthioanthraquinone, 4-methylbenzophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 1-hydroxy-cyclohexyl-phenyl ketone.

[0052] Furthermore, a super wear resistant agent is obtained by ultraviolet light treatment, and its specific parameters are not particularly limited. According to an embodiment of the present invention, in the ultraviolet light treatment step, the power of the ultraviolet light is 35-100W, and the time is 1-24h.

[0053] The working principle of the bionic flake super wear-resistant agent prepared in the present invention is as follows Figure 2 As shown in , after applying the super wear-resistant agent with a particle brush structure to the surface of the material, a bionic scale structure is formed. From the perspective of the wear resistance mechanism, the wear-resistant material needs to have good affinity (mutual solubility) with the adhesive material (polymer material), and it itself has a lubricating component, which reduces the friction coefficient and can significantly improve the wear resistance. In the present invention, a super wear-resistant agent can be efficiently prepared by a simple preparation method. The obtained super wear-resistant agent can form a bionic scale structure on the application surface due to the self-assembly of nanosheets tending to the minimum interface energy morphology. It not only has excellent wear resistance, excellent gloss, resistance to dry and wet rubbing, and flexibility, but also has excellent adhesion and waterproof and anti-pollution capabilities. At the same time, it can increase the feel of the product, making the product softer, more natural, smooth and delicate.

[0054] The present invention is described below by means of specific examples. It should be noted that the following specific examples are only for illustrative purposes and do not limit the scope of the present invention in any way. In addition, unless otherwise specified, methods without specific conditions or steps are conventional methods, and the reagents and materials used can be obtained from commercial channels.

[0055] Example 1

[0056] 1 g of silica nanosheet powder was dispersed in a mixed solution of 100 mL of ethanol and 30 mL of water, and ammonia water was added to adjust the pH to 10 to form dispersion A;

[0057] Add 0.2 g of γ-methacryloxypropyltriethoxysilane to dispersion A, react at room temperature, and filter to obtain double-bond modified silica nanosheet powder particles;

[0058] The double bond-modified silica nanosheet powder particles were mixed into 2 g of mercapto-terminated water-soluble polysiloxane (molecular weight 200), and 0.2 g of 1-hydroxy-cyclohexyl-phenyl ketone was added, and the mixture was mixed evenly to form a dispersion B;

[0059] Treat with 35W ultraviolet light for 24 hours to make dispersion B into a paste-like wear-resistant agent.

[0060] Figure 3 The SEM image of the silicon dioxide nanosheet powder in this embodiment is shown in FIG. 1 , and it can be seen that its microstructure is nanosheets. The SEM characterization results of the super wear resistant agent in this embodiment are as follows: Figure 4 As shown, through Figure 4 and Figure 3 By comparison, it can be seen that after the silica nanosheets were grafted with water-soluble polysiloxane particle brushes, the dispersibility was improved and no Figure 3 The phenomenon of sheet stacking in the middle, and the conductivity of silica nanosheets becomes poor after the polymer is grafted on the surface, which reduces the edge resolution of the nanosheets.

[0061] Example 2

[0062] 2 g of silica nanosheet powder was dispersed in a mixed solution of 100 mL of ethanol and 30 mL of water, and ammonia water was added to adjust the pH to 10 to form dispersion A;

[0063] Add 0.4 g of γ-methacryloxypropyltriethoxysilane to dispersion A, react at room temperature, and filter to obtain double-bond modified silica nanosheet powder particles;

[0064] The double-bond modified silica nanosheet powder particles were mixed into 2 g of mercapto-terminated water-soluble polysiloxane (molecular weight 200), and 0.2 g of 1-hydroxy-cyclohexyl-phenyl ketone was added, and the mixture was mixed evenly to form a dispersion B;

[0065] Treat with 35W ultraviolet light for 24 hours to make dispersion B into a paste-like wear-resistant agent.

[0066] The SEM results of the coating obtained after applying the super wear resistant agent in this example to the leather surface show that Figure 5 As shown, through Figure 5 It can be seen that the wear-resistant agent forms a continuous wear-resistant layer with a bionic scale structure on the leather surface.

[0067] Example 3

[0068] 1 g of silica nanosheet powder was dispersed in a mixed solution of 100 mL of ethanol and 30 mL of water, and ammonia water was added to adjust the pH to 10 to form dispersion A;

[0069] Add 0.2 g of γ-methacryloxypropyltriethoxysilane to dispersion A, react at room temperature, and filter to obtain double-bond modified silica nanosheet powder particles;

[0070] The double-bond modified silica nanosheet powder particles were mixed into 2 g of mercapto-terminated water-soluble polysiloxane (molecular weight 400), and 0.2 g of 1-hydroxy-cyclohexyl-phenyl ketone was added, and the mixture was mixed uniformly to form a dispersion B;

[0071] Treat with 35W ultraviolet light for 24 hours to make dispersion B into a paste-like wear-resistant agent.

[0072] The SEM results of the coating obtained after applying the super wear-resistant agent in this example to the surface of textile fibers are as follows: Figure 6 As shown, through Figure 6 It can be seen that the wear-resistant agent can also form a wear-resistant coating with a complete bionic scale structure on a rough surface similar to textile fibers.

[0073] Example 4

[0074] 1 g of silica nanosheet powder was dispersed in a mixed solution of 100 mL of ethanol and 30 mL of water, and ammonia water was added to adjust the pH to 10 to form dispersion A;

[0075] Add 0.2 g of γ-methacryloxypropyltriethoxysilane to dispersion A, react at room temperature, and filter to obtain double-bond modified silica nanosheet powder particles;

[0076] The double-bond modified silica nanosheet powder particles were mixed into 2 g of mercapto-terminated water-soluble polysiloxane (molecular weight 200), and 0.1 g of 1-hydroxy-cyclohexyl-phenyl ketone was added, and the mixture was mixed evenly to form a dispersion B;

[0077] Treat with 35W ultraviolet light for 24 hours to make dispersion B into a paste-like wear-resistant agent.

[0078] Example 5

[0079] 1 g of silica nanosheet powder was dispersed in a mixed solution of 90 mL of ethanol and 40 mL of water, and ammonia water was added to adjust the pH to 11 to form dispersion A;

[0080] Add 0.2 g of γ-methacryloxypropyltriethoxysilane to dispersion A, react at room temperature, and filter to obtain double-bond modified silica nanosheet powder particles;

[0081] The double-bond modified silica nanosheet powder particles were mixed into 2 g of mercapto-terminated water-soluble polysiloxane (molecular weight 400), and 0.2 g of 1-hydroxy-cyclohexyl-phenyl ketone was added, and the mixture was mixed uniformly to form a dispersion B;

[0082] Treat with 35W ultraviolet light for 24 hours to make dispersion B into a paste-like wear-resistant agent.

[0083] Example 6

[0084] 4 g of silica nanosheet powder was dispersed in a mixed solution of 100 mL of ethanol and 30 mL of water, and ammonia water was added to adjust the pH to 10 to form dispersion A;

[0085] Add 0.8 g of γ-methacryloxypropyltriethoxysilane to dispersion A, react at room temperature, and filter to obtain double-bond modified silica nanosheet powder particles;

[0086] The double-bond modified silica nanosheet powder particles were mixed into 5 g of mercapto-terminated water-soluble polysiloxane (molecular weight 1000), and 0.4 g of 4-methylbenzophenone was added, and the mixture was mixed evenly to form a dispersion B;

[0087] Treat with 35W ultraviolet light for 24 hours to make dispersion B into a paste-like wear-resistant agent.

[0088] Comparative Example 1

[0089] The same implementation method as Example 1 is adopted, except that the silicon dioxide powder used is spherical silicon dioxide nanoparticles with a particle size between 80-100 nm.

[0090] Comparative Example 2

[0091] The same implementation method as in Example 2 was adopted, except that a mercapto-terminated water-insoluble polysilane (molecular weight of 200) was used.

[0092] Comparative Example 3

[0093] Comparative Example 3 is a leather wear-resistant agent purchased randomly from the market.

[0094] Test Case

[0095] The wear-resistant agents in Examples 1-3 and Comparative Examples 1-3 were applied to leather samples cut with scissors using an applicator, and the wear resistance of the coated leathers was tested. The test results are shown in Table 1.

[0096] Table 1 Wear resistance agent performance test results

[0097]

[0098] Note: The test methods for each test item in Table 1 are:

[0099] (1) Wear resistance: QB / T 2726-2005;

[0100] (2) Water vapor permeability: QB / T 1811-93.

[0101] It can be seen from the test results in Table 1 that 1. Silica as a wear-resistant material can effectively increase the hardness of the wear-resistant agent; 2. Compared with spherical particles, the bionic flaky structure formed in the present invention can improve adhesion; 3. Water-based polysiloxane effectively increases the wear resistance and water vapor permeability of the wear-resistant agent.

[0102] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0103] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a bionic scale super wear-resistant agent for textile leather, characterized in that: The following steps are involved: Provide a silicon dioxide nanosheet powder and a liquid mercapto-terminated water-soluble polysiloxane, wherein the silicon dioxide nanosheet powder has a thickness of 3-100 nm and a size of 0.5-50 μm; and the water-soluble polysiloxane has a molecular weight Mn of 100-4000; The silica nanosheet powder is dispersed in an alcohol-water mixed solution with a pH of 8-12 to form a dispersion; a double-bond-containing silane coupling agent is then added to the dispersion to react and modify the silica nanosheet powder at room temperature to obtain double-bond-modified silica nanosheet powder particles; The double-bond modified silica nanosheet powder particles are mixed into the liquid mercapto-terminated water-soluble polysiloxane, and a UV initiator is added. After being mixed evenly, the mixture is treated with UV light, and a paste-like wear-resistant agent is obtained through a click chemistry reaction. The bionic scale super wear-resistant agent is a silica nanosheet grafted water-soluble polysiloxane particle brush.

2. The preparation method according to claim 1, characterized in that In the alcohol-water mixed solution, the volume ratio of alcohol to water is 1-20, and the alcohol is a water-soluble low molecular weight alcohol with a molecular weight of 46-1000.

3. The preparation method according to claim 1, characterized in that: The amount of the double-bond-containing silane coupling agent added is 0.1%-20% of the mass of the silicon dioxide nanosheet powder; The double bond-containing silane coupling agent is selected from one or more of γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, vinyltrimethoxysilane, and vinyltri(β-methoxyethoxy)silane.

4. The preparation method according to claim 1, characterized in that: The amount of the liquid mercapto-terminated water-soluble polysiloxane added is 30%-400% of the mass of the silicon dioxide nanosheet powder.

5. The preparation method according to claim 1, characterized in that: The amount of the ultraviolet light initiator added is 10%-40% of the molar amount of the liquid mercapto-terminated water-soluble polysiloxane; The ultraviolet light initiator is selected from one or more of isopropylthioxanthinequinone, 4-methylbenzophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 1-hydroxy-cyclohexyl-phenyl ketone.

6. The preparation method according to claim 1, characterized in that: In the step of ultraviolet light treatment, the power of ultraviolet light is 35-100W and the time is 1-24h.

7. A bionic scale super wear-resistant agent for textile leather, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 6.